2007
DOI: 10.1002/pros.20581
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of two paclitaxel‐resistant prostate cancer cell lines and the mechanisms of paclitaxel resistance with two cell lines

Abstract: Background. Although paclitaxel is used for hormone-resistant prostate cancer, relapse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
181
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(190 citation statements)
references
References 33 publications
6
181
2
Order By: Relevance
“…Due to recent reports of decreased methylation of the downstream ABCB1 promoter in association with drug resistance, [4][5][6][7]10,25 we next investigated this mechanism as the possible cause of increased ABCB1 expression in our drug-resistant cell lines. Most of the variation in the degree of promoter methylation within drug-sensitive cell lines (including MCF-7 DOX-2 , MCF-7 EPI and MCF-7 TAX-2 cells selected to dose-8 and MCF-7 CC cells 'selected' to dose-12) occurred within the first 30 CpG sites (Figures 3d and 5a), which is consistent with the bisulfite sequencing data for MCF-7 cells reported by David et al 8 Significantly decreased methylation of the ABCB1 downstream promoter was observed in MCF-7 EPI cells at the onset of drug resistance (selection dose-9) both in terms of average promoter methylation (Figure 3a) and methylation across specific CpG sites (Figures 3e and 5c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to recent reports of decreased methylation of the downstream ABCB1 promoter in association with drug resistance, [4][5][6][7]10,25 we next investigated this mechanism as the possible cause of increased ABCB1 expression in our drug-resistant cell lines. Most of the variation in the degree of promoter methylation within drug-sensitive cell lines (including MCF-7 DOX-2 , MCF-7 EPI and MCF-7 TAX-2 cells selected to dose-8 and MCF-7 CC cells 'selected' to dose-12) occurred within the first 30 CpG sites (Figures 3d and 5a), which is consistent with the bisulfite sequencing data for MCF-7 cells reported by David et al 8 Significantly decreased methylation of the ABCB1 downstream promoter was observed in MCF-7 EPI cells at the onset of drug resistance (selection dose-9) both in terms of average promoter methylation (Figure 3a) and methylation across specific CpG sites (Figures 3e and 5c).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ABCB1 promoter has been shown to be hypomethylated in several drug-resistant sub-lines of human leukemia (CCRF-CEM and HL60), 4,5 human epidermoid (KB3-1) 6 and prostate cancer (DU145) cells. 7 Similarly, one study examined differences in methylation between the ABCB1 5 0 -untranslated regions of drug-resistant and drugsensitive breast cancer cells. 8 This study established a correlation between increased ABCB1 expression and hypomethylation of the ABCB1 promoter by comparing the methylation of CpG dinucleotides within the ABCB1 downstream promoters of MCF-7 and MCF-7/ADR cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several taxane resistant cell lines have been generated in lung, ovarian, prostatic, breast, and gastric cancers (Chu et al 2000 ;Okugawa et al 2004;Duan et al 2005;Takeda et al 2007;Zhang et al 2010). However, establishment of esophageal cancer is limited; only a single study has been reported (Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…4B) The PC-3 cells were chosen to test whether these differences in efflux could be caused by different ABC transporters being responsible for the efflux of marizomib and NPI-0047. This cell line was used for this study because it is known to express members of the MRP family of multidrug efflux pumps (Zalcberg et al, 2000;Takeda et al, 2007). As a positive control to confirm the presence of an MRP efflux transporter, the cells were incubated for 1 h with 5 M fluorescein, a known MRP substrate, in the absence or presence of …”
Section: Evaluation Of Proteasome Inhibition Bymentioning
confidence: 99%